Evaluative Techniques in Consumer Finance–Experimental Results and Policy Implications for Financial Institutions - Apilado, Vincent P.; Warner, Don C.; Dauten, Joel J. (Journal of Financial and Quantitative Analysis, 1974)
Vincent P. Apilado, Don C. Warner, Joel J. Dauten, Evaluative Techniques in Consumer Finance–Experimental Results and Policy Implications for Financial Institutions, The Journal of Financial and Quantitative Analysis, Vol. 9, No. 2 (Mar., 1974), pp. 275-283